Modern Islamic Civilization and the Characteristics of Civilizing Language - Mohsen alviri; Shahnaz karimzadeh sureshjani (مطالعات بنیادین تمدن نوین اسلامی, 2022)
Modern Islamic civilization is one of the emerging issues of the Islamic world, that for developing and reinforcing the civilization, its supporters try to consider all the material and spiritual capacities that are effective in formation, improvement, and permanence of the civilization in expanding opinions, presenting considered models, identifying problems and theoretical understanding. One of the spiritual factors worthy of attention in the formation and expansion of a civilization is the civilization-building language which has some characteristics and attributes that will play a role in the consistency, cohesion and sustainability of a civilization against the competing and invading rivals, and with the absence of that, advanced human life will be leveled with animals. Relying on the capabilities and characteristics of such language can provide the ground for the consistency and cohesion of dominant civilization in the future of the Islamic world. The present paper intends to answer this question by descriptive-analytical method: What are the characteristics of civilization-building language? The findings of this study indicate that evolution and responsiveness in time, openness and applicability, generality and inclusiveness, creativity and dynamics and reception are among the characteristics of the civilization-building language, such language will be able to respond to the needs of a large and independent social unit and play an effective role in protecting civilizational capitals and presenting new ones.